Pengembangan E-Modul Pembelajaran Kimia Berbasis PBL Pada Materi Larutan Elektrolit Dan Non Elektrolit - Beatrix Elviati; Nursina Sya’bania; Apriani Megati (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research is a development research that aims to develop PBL-based chemistry learning E-Modules on electrolyte and non-electrolyte solution materials that are valid, practical and effective for use in the learning process. The development model used in this study refers to the Hannafin and Peck development model which consists of 3 stages, namely: (1) needs analysis (Needs Assessment), design stage (Design), and development/implementation stage (Develop and Implementation). This learning E-Module has gone through the validation stage by validators/experts and has gone through small-scale trials and field trials so as to produce a learning E-Module that is valid, practical and effective. Based on the results of data analysis, the average validity of the material was 0.91 and the validity of the media was 0.92 and was in the valid category. The practicality of the E-Module is obtained from the assessment of observers by 100% being in the very practical category, teacher responses of 94.64% and being in the very practical category, and student responses of 91% and being in the practical category. The effectiveness of the E-Module was obtained by 86.36% of students who achieved learning completeness scores. Based on the results of the study, it was concluded that the development of PBL-based chemistry learning E-Modules on electrolyte and non-electrolyte solution materials developed was valid, practical and effective for use in learning.